A point mutation within a distinct conserved region of the herpes simplex virus DNA polymerase gene confers drug resistance. - Hwang, C B (1992)
We have shown that a drug-resistant mutant from a clinical isolate of herpes simplex virus contains a single point mutation in the DNA polymerase gene that confers resistance to both acyclovir and foscarnet. The mutated amino acid is located within a distinct conserved region shared among alpha-like DNA polymerases which we designate region VII. We infer that these conserved sequences are directly or indirectly involved in the recognition and binding of nucleotide and PPi substrates.